Effects of nanoclay on properties of rice husk ash/ kaolin-based geopolymer coating composites - Nasrudin, Nurul Reffa Azyan (2017)
Research was done to investigate whether the addition of nanoclay influenced the properties of the rice husk ash/kaolin based geopolymer coating composite in fire resistance and bond strength. This geopolymer coating composite that mostly consists of silicon and aluminium are activated by alkaline activator which are the combination of sodium silicate (Na2SiO3) solution and sodium hydroxide (NaOH) solution to produce the coating resin. The preliminary works were initially done in order to obtain the best mixture proportions of geopolymer coating composite. The sodium hydroxide molarity of 8 M, 1.0 ratio solid to liquid and 5.5 ratio of alkaline activator were chosen as the control parameters while the ratio between rice husk ash and kaolin was varied. The fire-retardant test results showed that with 20:80 of rice husk ash to kaolin, better fire performance was obtained as the temperature at equilibrium of that coating is 230°C. The fire performance of geopolymer coating composite improved with nanoclay addition and the maximum of bond strength obtained was 3.48 MPa. These performances were seen in samples with 3 wt. % of nanoclay addition. However, the adhesion strength of the geopolymer coating composites were not majorly affected by nanoclay addition.